Clinical pathways as a healthcare tool: design, implementation and assessment of a clinical pathway for lower-extremity deep venous thrombosis. Issue 4 (3rd August 2009) - Verdú, A; Maestre, A; López, P; Gil, V; Martín-Hidalgo, A; Castaño, J A
Abstract : Objective: To design, implement and assess a clinical pathway for lower-extremity deep venous thrombosis, and to compare the length of hospital stay in two different periods. Design: Development of the care pathway by a multidisciplinary team, followed by a controlled intervention study to compare two non-concomitant cohorts of patients corresponding to the years 2002 (before the implementation of the critical pathway) and 2004 (year of the implementation). Setting: Academic tertiary care hospital. Participants: 90 patients, 42 corresponding to the year 2004 and 48 to 2002, admitted to hospital with a diagnosis of lower-extremity deep venous thrombosis (DVT). Main outcome measures: Length of hospital stay, hospitalisation costs and care indicators. Results: The mean length of hospital stay was 6.78 days in 2002 and 4.72 days in 2004. This means a reduction of 2.06 days (p<0.012). The reduction in the length of hospital stay in 2004 situates the hospital 1.98 days below the mean stay of our community (6.7 days) for the same diagnosis and year. The impact of the clinical pathway was assessed using the following indicators: implementation indicator 92.2%, compliance indicator 65%, adverse events indicator 2.5% and satisfaction indicator 67%. In comparison with costs incurred in year 2002, implementation of the clinical pathway resulted in a saving of €427.33 per patient and a total saving of €17 093.20. Conclusions: The implementation of a lower-extremity DVT clinical pathway in our institution has help to reduce hospitalisation costs, due to a decreased length of hospital stay.